Study protocol: randomised controlled hybrid type 2 trial evaluating the scale-up of two arts interventions for postnatal depression and Parkinson's disease. Issue 2 (1st February 2022) - Soukup, Tayana; Davis, Rachel E; Baldellou Lopez, Maria; Healey, Andy; Estevao, Carolina; Fancourt, Daisy; Dazzan, Paola; Pariante, Carmine; Dye, Hannah; Osborn, Tim; Bind, Rebecca; Sawyer, Kristi; et al.
Abstract : Introduction: Research on the benefits of 'arts' interventions to improve individuals' physical, social and psychological well-being is growing, but evidence on implementation and scale-up into health and social care systems is lacking. This protocol reports the SHAPER-Implement programme (Scale-up of Health-Arts Programmes Effectiveness-Implementation Research), aimed at studying the impact, implementation and scale-up of: Melodies for Mums (M4M), a singing intervention for postnatal depression; and Dance for Parkinson's (PD-Ballet) a dance intervention for Parkinson's disease. We examine how they could be embedded in clinical pathways to ensure their longer-term sustainability. Methods and analysis: A randomised two-arm effectiveness-implementation hybrid type 2 trial design will be used across M4M/PD-Ballet. We will assess the implementation in both study arms (intervention vs control), and the cost-effectiveness of implementation. The design and measures, informed by literature and previous research by the study team, were refined through stakeholder engagement. Participants (400 in M4M; 160 in PD-Ballet) will be recruited to the intervention or control group (2:1 ratio). Further implementation data will be collected from stakeholders involved in referring to, delivering or supporting M4M/PD-Ballet (N=25–30 for each intervention). A mixed-methods approach (surveys and semi-structured interviews) will be employed. 'Acceptability' (measured by the 'Acceptability Intervention Measure') is the primary implementation endpoint for M4M/PD-Ballet. Relationships between clinical and implementation outcomes, implementation strategies (eg, training) and outcomes will be explored using generalised linear mixed models. Qualitative data will assess factors affecting the acceptability, feasibility and appropriateness of M4M/PD-Ballet, implementation strategies and longer-term sustainability. Costs associated with implementation and future scale-up will be estimated. Ethics and dissemination: SHAPER-PND (the M4M trial) and SHAPER-PD (the PD trial) are approved by the West London and GTAC (20/PR/0813) and the HRA and Health and Care Research Wales (REC Reference: 20/WA/0261) Research Ethics Committees. Study findings will be disseminated through scientific peer-reviewed journals and scientific conferences. Trial registration numbers: Both trials are registered with NIH US National Library of Medicine, ClinicalTrials.gov. The trial registration numbers, URLs of registry records, and dates of registration are: (1) PD-Ballet: URL: NCT04719468 (https://eur03.safelinks.protection.outlook.com/?url=https%3A%2F%2Fwww.clinicaltrials.gov%2Fct2%2Fshow%2FNCT04719468%3Fterm%3DNCT04719468%26draw%3D2%26rank%3D1&data=04%7C01%7Crachel.davis%40kcl.ac.uk%7C11a7c5142782437919f808d903111449%7C8370cf1416f34c16b83c724071654356%7C0%7C0%7C6375441942616 ) (date of registration: 22 Jan 2021). (2) Melodies for Mums: NCT04834622 (https://clinicaltrials.gov/ct2/show/NCT04834622?term=shaper-pnd&draw=2&rank=1 ) (date of registration: 8 Apr 2021).